EFEKTIVITAS PENDIDIKAN KESEHATAN CUP CAKE BBW (BROKOLI, BAYAM DAN WORTEL) SEBAGAI MAKANAN RENDAH KALORI TERHADAP PENGETAHUAN PASIEN DIABETES MELLITUS TIPE 2 - Mira Khairunnisa; Yesi Hasneli; Bayhakki Bayhakki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The purpose of this study is to identify the effectivity of health education cup cake BBW as Low Calorie Food to Diabetes Mellitus type 2 Patient. The research used pre-eksperimental design without control group. Participants of this study were 34 people. Sample taken using non probability sampling technique using purposive sampling. Instrument used in this study was a questionnaire about as Low Calorie Food to Diabetes Mellitus type 2 Patient. The participants group were given health education cup cake BBW. Data analyzed using Wilcoxon test. The results of the study shows that level of knowledge before intervention is 10,74 with maximal and minimal value 6 and 15 and after is 22,50 with maximal and minimal value 16 and 25 (p value = 0,000), it mean that there is an increase knowledge after received information about cup cake BBW. The results of this study commen that healt education cup cake BBW can increase patient’s knowledge about Low Calorie Food to Diabetes Mellitus type 2 Patient. The finding of this study can be used of nursing intervention to increase patient’s knowledge Low Calorie Food to Diabetes Mellitus type 2 Patient.Keywords: Cup Cake BBW , Diabetes mellitus Type 2, Health Education